2002
DOI: 10.1017/s0022336000057814
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician [Dobrotivian (Llandeillian Stage) to Ashgill] crinoids (phylum Echinodermata) from the Montes de Toledo and Sierra Morena, Spain with implications for paleogeography of Peri-Gondwana

Abstract: Seven crinoid species and one very unusual column are recognized from the Ordovician, Dobrotivian (Llandeillian Stage) to Ashgill of Spain. Three previously described species, Heviacrinus melendezi Gil Cid, Domínguez, and Silván, 1996; Coralcrinus sarachagorum Gil Cid, Domínguez, and Silván, 1998; and Ortsaecrinus cocae Gil Cid, Domínguez, Torres, and Jiménez, 1999, are considered, and four new species assigned to three new genera are described herein, including Visocrinus castelli, Fresnedacrinus ibericus, Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Ausich (in review comments, forwarded to S. K. D. on 18 February 2010) has brought to our attention the similarity of the Oman material to Llanvirn Heviacrinus melendezi Gil Cid, Domínguez Alonso and Silván Pobes, 1996 (see also Ausich et al . 2002, 2007) from Spain, a disparid genus lacking an anal sac.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Ausich (in review comments, forwarded to S. K. D. on 18 February 2010) has brought to our attention the similarity of the Oman material to Llanvirn Heviacrinus melendezi Gil Cid, Domínguez Alonso and Silván Pobes, 1996 (see also Ausich et al . 2002, 2007) from Spain, a disparid genus lacking an anal sac.…”
mentioning
confidence: 97%
“…Gil Cid et al . (1996, p. 20) originally assigned the genus Heviacrinus to the family Iocrinidae, whereas Ausich et al . (2002, p. 989) moved it to the family Maennilicrinidae Ausich of the order Maennilicrinida Ausich in strict accordance with Ausich’s (1998) system of classification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…obs. ); Pizarras Cantera Formation, El Viso del Marqués, Ciudad Real Province, Spain (Gil Cid et al 1996, Arroyo & Lara 2002, Ausich et al 2002.…”
Section: Dendrocystites Barrandeimentioning
confidence: 99%
“…Thus the presence of Trocholites fugax in the Prague Basin, Iberian Chain and Armorican Massif are coeval, suggesting that faunal exchange took place between these areas during the early Dobrotivian, which is in agreement with the conclusions of Havlíček et al (1994). More recently Ausich et al (2002) described a Dobrotivian echinoderm fauna from the Iberian Chain and suggested that there was faunal isolation between peri-Gondwana and Perunica. In addition, Evans (2000) noted the presence of Trocholites even in the Middle Ordovician of Bolivia, Northwestern Gondwana, but this material has not yet been described nor figured.…”
Section: Palaeobiogeographical Significance Of Trocholitesmentioning
confidence: 99%